2017
DOI: 10.1109/jbhi.2016.2612059
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Motion Artifact Detection Algorithm for Accurate Detection of Heart Rates From Photoplethysmographic Signals Using Time–Frequency Spectral Features

Abstract: Motion and noise artifacts (MNAs) impose limits on the usability of the photoplethysmogram (PPG), particularly in the context of ambulatory monitoring. MNAs can distort PPG, causing erroneous estimation of physiological parameters such as heart rate (HR) and arterial oxygen saturation (SpO2). In this study, we present a novel approach, "TifMA," based on using the time-frequency spectrum of PPG to first detect the MNA-corrupted data and next discard the nonusable part of the corrupted data. The term "nonusable"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 31 publications
0
53
0
Order By: Relevance
“…Movement artifacts affect both the PPG and noninvasive BP. Although noise reduction in the PPG is an active field of study, sophisticated techniques of signal reconstruction during movement have focused on accurate estimations of heart rate [39], [40]. PPG motion artifact reduction remains a challenging task.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Movement artifacts affect both the PPG and noninvasive BP. Although noise reduction in the PPG is an active field of study, sophisticated techniques of signal reconstruction during movement have focused on accurate estimations of heart rate [39], [40]. PPG motion artifact reduction remains a challenging task.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Third, there are many methods for improving smartphone PPG accuracy [27,[29][30][31][32][33]. For example, adding a suitable bandpass filter for signal processing [28] or excluding data with RR intervals that differ more than a certain threshold [70] are simple and effective approaches to reduce noise.…”
Section: Limitationsmentioning
confidence: 99%
“…Given that smartphones with in-built cameras have become a part of modern life, using them to access health information is an ideal alternative when ECGs or similar medical devices are not available [26]. In addition, there have been several reported techniques for increasing the accuracy of smartphone PPG, such as point-of-interest selection [27], bandpass filtering [28], adaptive signal thresholding [29], motion detection techniques [30][31][32], interpolation techniques [33], and signal decomposition methods [34][35][36]. Bioengineering studies indicate that the average HR [37] and HRV measured using smartphone PPG are comparable with those measured using gold standard ECGs [21,28,[38][39][40].Although it is a promising solution for practical data collection and has an accuracy that has been well proved in several experiments, using smartphone PPG to measure HRV has received limited research attention in applied disciplines such as medicine or psychology [41]; a possible explanation is the lack of robustness in practical scenarios.…”
mentioning
confidence: 99%
“…Vital signs extraction along with the other physiological parameters, which is generated using the pulse oximetry, is already predicted on the given artifact free motion photoplethysmogram data. It is also known that photoplethysmogram signals are the high-sensitive data to the artifacts specially the one which is recorded when the patient were in motion [10] and this phenomena has the restricted use of the photoplethysmogram for application of ambulatory monitoring. Moreover, motion and noise artifacts also known as MNAs leads to the estimation of SPO2 and HR [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that photoplethysmogram signals are the high-sensitive data to the artifacts specially the one which is recorded when the patient were in motion [10] and this phenomena has the restricted use of the photoplethysmogram for application of ambulatory monitoring. Moreover, motion and noise artifacts also known as MNAs leads to the estimation of SPO2 and HR [10]. However the various sensors may be able to minimize the motion disturbance and it makes sure that sensor are placed securely and it is found that they are not enough capable for removing the MNA.…”
Section: Introductionmentioning
confidence: 99%